Microwave synthesis and characterization Mg(OH)2/Gr nanocomposites in the presence of sodium dodecyl sulfate (SDS) as a stabilizer agent - Enayatollah Sheikhhosseini; Mehdi Ranjbar (Elsevier, 2019)
This work reports, microwave synthesis and characterization Mg(OH)2/Gr nanocomposites in the presence of sodium dodecyl sulfate (SDS) as a stabilizer agent. Mg(OAc)2•4H2O and graphene powder have been used as starting reagents. Mg(OH)2/Gr nanocomposites synthesized by microwave method, particle size distribution and characterization of products were done by X-ray diffraction (XRD), Atomic force microscopy (AFM), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Uv-Vis and IR spectroscopy. The results indicated that the synthesized Mg(OH)2/Gr nanocomposites have a pure crystality structure with average size 75-110 nm. Keywords: Mg(OH)2/Gr, Nanocomposites, Microwave method, Optical investigation